Potentials of tourism development in the Lower Neretva region - Šetka, Josip; Pejdo, Ana (Turizam, 2023)
The Lower Neretva region stands out as a unique area on the Croatian coast due to its landscape peculiarities. It is administratively divided into three towns: Metković, Ploče and Opuzen and four municipalities: Slivno, Kula Norinska, Zažablje and Pojezerje, and it is also an integral part of Dubrovnik-Neretva County. This region has an area of about 412,56 km2. The main objective of this paper was to investigate what potential forms of tourism are suitable for development and further investment in this area. It also aimed to show applicability of ArcGIS computer software in the function of tourism development. An online survey was conducted, with the main purpose to examine the opinions and attitudes of the local people about the current state and development potential of tourism in this region. The purpose of this research is to create the clearest vision for future tourism development in the Lower Neretva region, as well as the development strategies that can serve in determining existing and future spatial planning documents.